Fertilization and plant density in genotypes of corn under rainy season conditions. - Cano, Octavio (2006)
During the rainy season in 1998/98 a reseach was conducted in Campo Experimental Cotaxtla, Veracruz, México, with the objectives of knowing the response of five corn genotypes to doses fertilizer and plant density. A completed randomized block experimental design with two replications was used arranged in split plots where the genotypes (G) VS-536, H-512, H-513, HTV1 and HTV2 were considered as small plots ; The medium plots were doses of fertilization (F) of N2,P2O5,K2O: 161-46-0, 184-69-0, 184-69-30, 207-92-0 and 207-92-30 ; and the big plots were plant densities(D): 50, 62.5, 75, 93.75, 100 and 125 thousand plants/hectare. The characteristics studied were: harvest index, ears per plant, and grain yield. The analysis of variance showed significant differences for some characteristics in D, F, DxF y DxG and for all in G. According to this, the best genotype was the experimental hybrid HTV1 with yield 6.74 t/ha. The response to fertilization was only of to harvest index, where the best dose was 184-69-0. In relation with plant density, with 62500 plants/hectare, all genotypes showed their best yield and number of ears per plant.